2011
DOI: 10.1016/j.ijgo.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency in Pakistani mothers and their newborns

Abstract: There was a high prevalence of vitamin D deficiency in the Pakistani parturients and their newborns. There was a correlation between higher maternal vitamin D levels and lower blood pressure in the mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 20 publications
2
62
3
1
Order By: Relevance
“…Pregnant women who did not receive vitamin D supplementation showed a reduction in circulating 25(OH)D levels during the third trimester compared with the first trimester (4,5). Several observational studies have reported that low maternal circulating 25(OH)D concentrations in pregnant women may have negative health consequences for both mothers and newborns (3,6).…”
mentioning
confidence: 99%
“…Pregnant women who did not receive vitamin D supplementation showed a reduction in circulating 25(OH)D levels during the third trimester compared with the first trimester (4,5). Several observational studies have reported that low maternal circulating 25(OH)D concentrations in pregnant women may have negative health consequences for both mothers and newborns (3,6).…”
mentioning
confidence: 99%
“…Vitamin D 3 is also derived from dietary sources such as oily fish, availability of which is often limited. Natural dietary sources of vitamin D 2 are also limited to some vegetables such as mushrooms, but both vitamin D 2 (12)(13)(14)(15). South Asia also has a high burden of respiratory tract infections among children (16,17).…”
mentioning
confidence: 99%
“…Maternal vitamin D deficiency occurs worldwide, even in sunny climates, and is a significant public health issue with prevalence rates ranging from 5 to 89% depending on the cutoff value used (Bodnar et al, 2007b;Greer, 2008;Prentice, 2008;Sahu et al, 2009;Yu et al, 2009;Hamilton et al, 2010;Agarwal and Arya, 2011;Hossain et al, 2011;Johnson et al, 2011;Vandevijvere et al, 2012;McAree et al, 2013;Andersen et al, in press). In a recent study in the US, an estimated 5 to 29% of pregnant women had inadequate vitamin D status with a higher prevalence in African Americans who are at a higher risk of vitamin D deficiency due to increased skin pigmentation which can decrease endogenous vitamin D production (Brannon and Picciano, 2011).…”
Section: Vitamin D In Pregnancy Placenta and Vascular Functionmentioning
confidence: 99%